Factors influencing participation of elderly population in mass drug administration for lymphatic filariasis: a cross-sectional study - Jabir, Muhammed; Balakrishnan, Vijayakumar; Krishnamoorthy, Kaliannagounder; Kumar, Ashwani; Abraham, Philip Raj (Frontiers in Pharmacology, 2024)
The success of mass drug administration (MDA) for lymphatic filariasis (LF) elimination relies on achieving a participation rate of at least 65% within the endemic community. However, participation of sub-population in the community varies and a significant treatment gap among the elderly population, remains to be addressed. The present study explores the factors influencing the elderly participation in MDA and propose possible solutions to bridge the gap.A cross-sectional study of individuals aged 60 years and above was conducted from August to December 2023 in Yadgiri district of Karnataka, which is endemic for LF. The participants were interviewed using a structured questionnaire, focusing on the perception about LF and MDA and drug consumption behaviours. STATA 14 software was used to analyse the data.We used a logistic regression model to determine the factors influencing drug consumption.The study included 315 elderly individuals with a mean age (SD) of 67.4 (6.2) years. Although, 58.4% of them received the drugs during the last round of MDA in 2023, only 40.6% consumed it. The drug refusal rate was 19.4%. Fear of side effects (22.9%) was cited as the primary reason for not accepting the drugs. Weak perception of LF transmission risk (25.7%) and mistrust of drug safety (42.5%) were reported as reasons for non-compliance. Logistic regression identified significant associations, including residence (peri-urban: OR = 6.80), chronic disease (diabetes: OR = 2.89), trust on drug safety (OR = 16.27), and opinion of neighbours (OR = 5.35).Participation of elderly population in MDA was suboptimal (40.6%). Tailored interventions to improve consumption such as addressing misconceptions, building trust in MDA and effective monitoring and management of adverse events are vital to enhance their participation. The National guidelines should have specific guidelines and strategies to address this issue to improve their participation in MDA for elimination of LF.